Transcriptomic and immunophenotypic profiling reveals molecular and immunological hallmarks of colorectal cancer tumourigenesis - Roelands, Jessica; van der Ploeg, Manon; Ijsselsteijn, Marieke E; Dang, Hao; Boonstra, Jurjen J; Hardwick, James C H; Hawinkels, Lukas J A C; Morreau, Hans; de Miranda, Noel F C C (Gut, 2023)
ObjectiveBiological insights into the stepwise development and progression of colorectal cancer (CRC) are imperative to develop tailored approaches for early detection and optimal clinical management of this disease. Here, we aimed to dissect the transcriptional and immunologic alterations that accompany malignant transformation in CRC and to identify clinically relevant biomarkers through spatial profiling of pT1 CRC samples.DesignWe employed digital spatial profiling (GeoMx) on eight pT1 CRCs to study gene expression in the epithelial and stromal segments across regions of distinct histology, including normal mucosa, low-grade and high-grade dysplasia and cancer. Consecutive histology sections were profiled by imaging mass cytometry to reveal immune contextures. Finally, publicly available single-cell RNA-sequencing data was analysed to determine the cellular origin of relevant transcripts.ResultsComparison of gene expression between regions within pT1 CRC samples identified differentially expressed genes in the epithelium (n=1394 genes) and the stromal segments (n=1145 genes) across distinct histologies. Pathway analysis identified an early onset of inflammatory responses during malignant transformation, typified by upregulation of gene signatures such as innate immune sensing. We detected increased infiltration of myeloid cells and a shift in macrophage populations from pro-inflammatory HLA-DR+CD204− macrophages to HLA-DR−CD204+ immune-suppressive subsets from normal tissue through dysplasia to cancer, accompanied by the upregulation of the CD47/SIRPα ‘don’t eat me signal’.ConclusionSpatial profiling revealed the molecular and immunological landscape of CRC tumourigenesis at early disease stage. We identified biomarkers with strong association with disease progression as well as targetable immune processes that are exploitable in a clinical setting.